Family Resilience of Indonesian Migrant Workers in Mataraman Region East Java Through the Lens of Maqāṣid al-Usrah - Muhamad Khoiri Ridlwan; Ahmad Zahro; Achmad Murtafi Haris; Mohammed Salim Salim; Evi Fitriana (MUSLIM HERITAGE, 2025)
This study explores the family resilience of Indonesian migrant worker (PMI) households in the Mataraman region of East Java through the integration of Froma Walsh’s family resilience theory and Jamāl al-Dīn ʿAṭiyyah’s maqāṣid al-usrah framework. Labor migration has restructured families, often placing women as temporary heads of households, thereby reshaping gender roles and spiritual responsibilities. Employing a qualitative-descriptive approach, the research draws on 24 in-depth interviews and group observations with PMI families. Findings identify three dominant resilience patterns: (1) collaborative, characterized by faith-based role negotiation grounded in amanah and shūrā; (2) externally supported, sustained through religious and kinship networks such as pengajian and yasinan; and (3) independent, emphasizing spiritual discipline and digital intimacy as acts of worship. Values of tawakkul (trust in God), sabr (patience), and ikhtiar (effort) form the belief system that anchors emotional and moral endurance. Integrating Walsh’s framework with maqāṣid al-usrah reveals an Islamic model of resilience that unites psychological adaptability, social solidarity, and theological intentionality. Thus, family resilience in Mataraman represents not merely coping behavior but a conscious act of faith and the realization of maqāṣid within transnational Muslim family life.   Abstrak Penelitian ini mengkaji ketahanan keluarga pekerja migran Indonesia (PMI) di wilayah Mataraman, Jawa Timur—meliputi Kediri, Tulungagung, Nganjuk, Ponorogo, Blitar, dan Trenggalek—dalam perspektif teori family resilience Froma Walsh dan konsep maqāṣid al-usrah Jamāl al-Dīn ʿAṭiyyah. Migrasi tenaga kerja menyebabkan perubahan struktur keluarga dan peran gender, di mana perempuan sering menjadi kepala keluarga sementara. Penelitian ini menggunakan metode kualitatif-deskriptif melalui 24 wawancara mendalam dan observasi kelompok keluarga PMI. Hasil penelitian menunjukkan tiga model utama ketahanan keluarga: (1) kolaboratif, dengan pembagian peran fleksibel berbasis amanah dan shūrā; (2) berbasis dukungan eksternal, melalui jaringan sosial dan kegiatan keagamaan seperti pengajian dan yasinan; serta (3) mandiri, yang menonjolkan disiplin spiritual dan komunikasi digital bernilai ibadah. Nilai-nilai tawakkul, sabr, dan ikhtiar menjadi sistem keyakinan utama yang menopang stabilitas emosional dan spiritual keluarga. Integrasi teori Walsh dan maqāṣid al-usrah menghasilkan model ketahanan keluarga Islam yang memadukan adaptasi psikologis, solidaritas sosial, dan kesadaran teologis. Dengan demikian, ketahanan keluarga dalam konteks Mataraman bukan sekadar kemampuan bertahan, tetapi wujud ibadah dan realisasi maqāṣid dalam kehidupan keluarga Muslim transnasional.